Bilateral Distal Femoral Nailing in a Rare Symmetrical Periprosthetic Knee Fracture - Carvalho, M (2014)
The authors report a case of a 78-year-old polytrauma patient, with severe thoracic trauma and bilateral symmetrical periprosthetic femoral fractures after a violent car accident. After the primary survey, with the thoracic trauma stabilized, neurovascular lesions excluded, and provisional immobilization applied, both fractures were classified as OTA: 33-A3, Rorabeck Type II, and closed reduction and internal fixation with distal femoral nails were performed. At 5 months of follow-up, the patient was able to walk with crutches and clear radiologic signs of fracture consolidation could be seen. At 24 months, the patient walked without any walking aid and had recovered her previous functional status. This surgical option allowed the authors to achieve relative stability using an intramedullary technique, preserving fracture hematoma in an osteopenic patient, and was found to be successful in recovering the patient’s previous functional status and satisfaction after major trauma.